Putative roles of mosquitoes (Culicidae) and biting midges (Culicoides spp.) as mechanical or biological vectors of lumpy skin disease virus. Issue 3 (7th May 2022) - Paslaru, Anca I.; Maurer, Lena M.; Vögtlin, Andrea; Hoffmann, Bernd; Torgerson, Paul R.; Mathis, Alexander; Veronesi, Eva
Abstract: The stable fly Stomoxys calcitrans (Diptera: Muscidae) is considered as the main mechanical vector of the lumpy skin disease virus (LSDV). In addition, the mosquito species Aedes aegypti (Diptera: Culicidae) was shown to transmit the virus from donor to receptor animals. Retention of the virus for several days was shown for two additional tropical mosquito species and the biting midge Culicoides nubeculosus (Diptera: Ceratopogonidae). In the present study, viral retention for 10‐ or 7‐days post feeding on virus‐spiked blood through a membrane was shown for field‐collected Aedes japonicus and laboratory‐reared Culex pipiens, two widely distributed mosquito species in temperate regions. Viral DNA could be detected from honey‐coated Flinders Technology Associates (FTA) cards and shedded faeces for 1 or 4 days after an infectious blood meal was given to Ae. aegypti . Virus increase over time and virus dissemination was observed in laboratory‐reared C. nubeculosus, but the virus could be isolated from field‐collected biting midges only from the day of exposure to the blood meal. Thus, mosquitoes might serve as mechanical vectors of LSDV in case of interrupted feeding. A putative biological virus transmission by Culicoides biting midges, as suspected from field observations, deserves further investigations. Abstract : Lumpy skin disease virus, mainly transmitted by Stomoxys calcitrans, was retained in different mosquito species for up to 10 days after feeding on virus‐spiked blood. Virus was detected from honey‐coated Flinders Technology Associates (FTA) cards (virus presumably deposited with saliva) and shedded faeces for 1 or 4 days, respectively, in the yellow fever mosquito Aedes aegypti . Virus propagation and dissemination was observed in laboratory‐reared Culicoides nubeculosus biting midges, but not in field‐collected Culicoides spp.